Prior optic neuritis detection on peripapillary ring scans using deep learning. Issue 11 (25th October 2022) - Motamedi, Seyedamirhosein; Yadav, Sunil Kumar; Kenney, Rachel C.; Lin, Ting‐Yi; Kauer‐Bonin, Josef; Zimmermann, Hanna G.; Galetta, Steven L.; Balcer, Laura J.; Paul, Friedemann; Brandt, Alexander U.
Abstract: Background: The diagnosis of multiple sclerosis (MS) requires demyelinating events that are disseminated in time and space. Peripapillary retinal nerve fiber layer (pRNFL) thickness as measured by optical coherence tomography (OCT) distinguishes eyes with a prior history of acute optic neuritis (ON) and may provide evidence to support a demyelinating attack. Objective: To investigate whether a deep learning (DL)‐based network can distinguish between eyes with prior ON and healthy control (HC) eyes using peripapillary ring scans. Methods: We included 1033 OCT scans from 415 healthy eyes (213 HC subjects) and 510 peripapillary ring scans from 164 eyes with prior acute ON (140 patients with MS). Data were split into 70% training, 15% validation, and 15% test data. We included 102 OCT scans from 80 healthy eyes (40 HC) and 61 scans from 40 ON eyes (31 MS patients) from an independent second center. Receiver operating characteristic curve analyses with area under the curve (AUC) were used to investigate performance. Results: We used a dilated residual convolutional neural network for the classification. The final network had an accuracy of 0.85 and an AUC of 0.86, whereas pRNFL only had an AUC of 0.77 in recognizing ON eyes. Using data from a second center, the network achieved an accuracy of 0.77 and an AUC of 0.90 compared to pRNFL, which had an AUC of 0.84. Interpretation: DL‐based disease classification of prior ON is feasible and has the potential to outperform thickness‐based classification of eyes with and without history of prior ON.